Isolation of a DNA probe for identification of Mycobacterium kansasii, including the genetic subgroup. - Yang, M (1993)
In order to develop a DNA-based assay to identify all Mycobacterium kansasii clinical isolates, a specific DNA probe was isolated in plasmid p6123. A total of 145 M. kansasii clinical isolates were collected from several countries and were examined with three probes by DNA hybridization. Of the 145 isolates, 115 (79%) were positive with the previously described probe pMK1-9 (Z. H. Huang, B. C. Ross, and B. Dwyer, J. Clin. Microbiol. 29:2125-2129, 1991), 129 (88%) were positive with the commercial Accu-probe assay (Gen-Probe), and 145 (100%) were positive with the p6123 probe. Southern blot analysis of EcoRI-digested M. kansasii chromosomal DNA with p6123 revealed that all Accu-probe-positive M. kansasii strains exhibited a 3-kb fragment, whereas all Accu-probe-negative M. kansasii strains displayed DNA fragments of variable molecular sizes. These results indicate that, unlike the previously described probes for M. kansasii, the fragment cloned into p6123 identified all 145 biochemically typical strains tested and provides an ideal target for future DNA-based speciation assays.